The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0004-282x2013000300009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative sensory testing in trigeminal traumatic neuropathic pain and persistent idiopathic facial pain

Abstract: The objective of this article was to investigate, with a systematic protocol of quantitative sensory testing, patients with persistent idiopathic facial pain (PIFP) and others with trigeminal traumatic neuropathic pain (TTN) compared to controls. Thirty patients with PIFP, 19 with TTN, and 30 controls were evaluated on subjective numbness and dysesthesia and with a systematic protocol of quantitative sensory testing for thermal evaluation (cold and warm), mechanical detection (touch and pinpricks for mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 23 publications
1
25
1
2
Order By: Relevance
“…[30][31][32] Also, in other facial pain conditions such as persistent idiopathic facial pain and trigeminal traumatic neuropathic pain, tactile threshold increments were already demonstrated. 33,34 Our measurements also revealed pathologic vibration sensing in TN patients preoperatively that contradicts the findings of Flor et al, but this discrepancy may be explained by the heterogeneous characteristics of the study population. 31 The latter trial included only TN subjects without prior invasive treatment that might influence sensory characteristics.…”
Section: Discussion Postinterventional Clinical Improvement and Procecontrasting
confidence: 68%
“…[30][31][32] Also, in other facial pain conditions such as persistent idiopathic facial pain and trigeminal traumatic neuropathic pain, tactile threshold increments were already demonstrated. 33,34 Our measurements also revealed pathologic vibration sensing in TN patients preoperatively that contradicts the findings of Flor et al, but this discrepancy may be explained by the heterogeneous characteristics of the study population. 31 The latter trial included only TN subjects without prior invasive treatment that might influence sensory characteristics.…”
Section: Discussion Postinterventional Clinical Improvement and Procecontrasting
confidence: 68%
“…Pain is described as deep, diffuse, continuous and persistent and may have burning or pressing sensation. Pain may be triggered by invasive dental 45,46 . Among etiologic factors involved with these conditions, one should stress dental implants, which have increased in frequency in general, and which may trigger PIFP or AO in predisposed patients 47,48 .…”
Section: Persistent Idiopathic Facial Pain (Pifp)mentioning
confidence: 99%
“…Treatment follows the same orientations of those recommended for NP in general 47,48 . Recent studies have shown that samples of PIFP and PPTPN patients had no significant differences as compared to different sensitivity parameters 45 and also that patients with AO have descending inhibitory pain system impairment 49 .…”
Section: Persistent Idiopathic Facial Pain (Pifp)mentioning
confidence: 99%
“…Subjective psychic factors play a major role in pain chronification and pain crises, especially when pain is located at the head and / or face, because of the psychic and social importance of this body area. Among orofacial pain diagnosis, atypical facial pain or persistent idiopathic facial pain (PIFP) remains as one of the most complex to evaluate and treat, with the compulsory need of psychological assessment 3 . PIFP is characterized as diffuse deep and constant chronic pain (International Headache Association, 2013) 4 that has no etiology behind it and the exclusion of other pathologies is necessary before final diagnosis.…”
Section: Introductionmentioning
confidence: 99%